To install click the Add extension button. That's it.

The source code for the WIKI 2 extension is being checked by specialists of the Mozilla Foundation, Google, and Apple. You could also do it yourself at any point in time. 4,5
Kelly Slayton
Congratulations on this excellent venture… what a great idea!
Alexander Grigorievskiy
I use WIKI 2 every day and almost forgot how the original Wikipedia looks like.
Live Statistics
English Articles
Improved in 24 Hours
Languages
Recent
Show all languages
What we do. Every page goes through several hundred of perfecting techniques; in live mode. Quite the same Wikipedia. Just better.
.
Leo
Newton
Brights
Milds # Hypothetical syllogism

In classical logic, hypothetical syllogism is a valid argument form which is a syllogism having a conditional statement for one or both of its premises.

An example in English:

If I do not wake up, then I cannot go to work.
If I cannot go to work, then I will not get paid.
Therefore, if I do not wake up, then I will not get paid.

The term originated with Theophrastus.

## Propositional logic

In propositional logic, hypothetical syllogism is the name of a valid rule of inference (often abbreviated HS and sometimes also called the chain argument, chain rule, or the principle of transitivity of implication). Hypothetical syllogism is one of the rules in classical logic that is not always accepted in certain systems of non-classical logic.[example  needed] The rule may be stated:

${\frac {P\to Q,Q\to R}{\therefore P\to R}}$ where the rule is that whenever instances of "$P\to Q$ ", and "$Q\to R$ " appear on lines of a proof, "$P\to R$ " can be placed on a subsequent line.

Hypothetical syllogism is closely related and similar to disjunctive syllogism, in that it is also type of syllogism, and also the name of a rule of inference.

## Formal notation

The hypothetical syllogism inference rule may be written in sequent notation, which amounts to a specialization of the cut rule:

${\frac {P\vdash Q\quad Q\vdash R}{P\vdash R}}$ where $\vdash$ is a metalogical symbol and $A\vdash B$ meaning that $B$ is a syntactic consequence of $A$ in some logical system;

and expressed as a truth-functional tautology or theorem of propositional logic:

$((P\to Q)\land (Q\to R))\to (P\to R)$ where $P$ , $Q$ , and $R$ are propositions expressed in some formal system.

## Proof

Step Proposition Derivation
1 $(P\to Q)\land (Q\to R)$ Given
2 $(\neg P\lor Q)\land (\neg Q\lor R)$ Material implication
3 $((\neg P\lor Q)\land \neg Q)\lor ((\neg P\lor Q)\land R)$ Distributivity
4 $((\neg P\lor Q)\land \neg Q)\lor R$ Conjunction elimination (3)
5 $((\neg P\land \neg Q)\lor (Q\land \neg Q))\lor R$ Distributivity
6 $\neg (Q\land \neg Q)$ Law of noncontradiction
7 $(\neg P\land \neg Q)\lor R$ Disjunctive syllogism (5,6)
8 $\neg P\lor R$ Conjunction elimination (7)
9 $P\to R$ Material implication

## Alternative forms

An alternative form of hypothetical syllogism, more useful for classical propositional calculus systems with implication and negation (i.e. without the conjunction symbol), is the following:

(HS1) $(Q\to R)\to ((P\to Q)\to (P\to R))$ Yet another form is:

(HS2) $(P\to Q)\to ((Q\to R)\to (P\to R))$ ### Proof

An example of the proofs of these theorems in such systems is given below. We use two of the three axioms used in one of the popular systems described by Jan Łukasiewicz. The proofs relies on two out of the three axioms of this system:

(A1) $\phi \to \left(\psi \to \phi \right)$ (A2) $\left(\phi \to \left(\psi \rightarrow \xi \right)\right)\to \left(\left(\phi \to \psi \right)\to \left(\phi \to \xi \right)\right)$ The proof of the (HS1) is as follows:

(1) $((p\to (q\to r))\to ((p\to q)\to (p\to r)))\to ((q\to r)\to ((p\to (q\to r))\to ((p\to q)\to (p\to r))))$ (instance of (A1))
(2) $(p\to (q\to r))\to ((p\to q)\to (p\to r))$ (instance of (A2))
(3) $(q\to r)\to ((p\to (q\to r))\to ((p\to q)\to (p\to r)))$ (from (1) and (2) by modus ponens)
(4) $((q\to r)\to ((p\to (q\to r))\to ((p\to q)\to (p\to r))))\to (((q\to r)\to (p\to (q\to r)))\to ((q\to r)\to ((p\to q)\to (p\to r))))$ (instance of (A2))
(5) $((q\to r)\to (p\to (q\to r)))\to ((q\to r)\to ((p\to q)\to (p\to r)))$ (from (3) and (4) by modus ponens)
(6) $(q\to r)\to (p\to (q\to r))$ (instance of (A1))
(7) $(q\to r)\to ((p\to q)\to (p\to r))$ (from (5) and (6) by modus ponens)

The proof of the (HS2) is given here.

### As a metatheorem

Whenever we have two theorems of the form $T_{1}=(Q\to R)$ and $T_{2}=(P\to Q)$ , we can prove $(P\to R)$ by the following steps:

(1) $(Q\to R)\to ((P\to Q)\to (P\to R)))$ (instance of the theorem proved above)
(2) $Q\to R$ (instance of (T1))
(3) $(P\to Q)\to (P\to R)$ (from (1) and (2) by modus ponens)
(4) $P\to Q$ (instance of (T2))
(5) $P\to R$ (from (3) and (4) by modus ponens)